Syria’s Christians and Facebook during the Armed Conflict (2011- 2015) - Sapag Muñoz de la Peña, Pablo; Rubio Moraga, Ángel Luis (Estudios sobre el Mensaje Periodístico, 2017)
During the armed crisis suffered by Syria since March 2011, the use of social networks as a communication tool is motivated by propaganda and humanitarian interests. This trend is evident among Syria’s Christians. This paper therefore focuses on two Facebook pages linked to this group. Using a content analysis, this article describes and analyzes the communication possibilities offered by social networks to specific groups in an environment of a multi-cause armed conflict in which religious sectarianism is relevant.